Religious and National Discourses Contradictory Belonging, Minorities, Marginality and Centrality - Acke, Hanna; Warnke, Ingo H.; Bonacchi, Silvia; Brylla, Seiler (Diskursmuster / Discourse Patterns, 2023)
The book introduces a new perspective on discursive categorisations in societies. We suggest a shift from minority/majority differentiations towards an analysis of marginalising and centralising discourses which leave room for contradictions and renegotiations of belonging. The interdisciplinary contributions study contradictory belonging to and within religious and national groups from the 18th century until today in diverse regional settings.